Relationship Between Resilience Sources & Job Satisfaction Post-Covid-19 In Indonesia: The Mediating Role of Vision, Purpose & Empathy - Mochammad Rivan Akhsa (Journal Research of Social Science, Economics, and Management, 2024)
This research explores the relationship between resilience sources and job satisfaction in post-COVID-19 Indonesia, emphasizing the mediating roles of vision, purpose, and empathy. Resilience, defined as the ability to adapt to adversity, has evolved from an individual trait to encompass organizational factors, especially in the context of significant disruptions like the COVID-19 pandemic. The study aims to fill existing literature gaps by analyzing how these resilience sources impact job satisfaction among Indonesian employees, thereby enhancing understanding of resilience in a local context. Using a quantitative approach, data were collected from 101 respondents, revealing a positive correlation between resilience and job satisfaction. Findings indicate that while resilience significantly predicts job satisfaction, vision, purpose, and empathy do not serve as effective mediators in this relationship. Additionally, age was found not to correlate with resilience, whereas senior managers exhibited higher resilience scores compared to lower-level employees. The research concludes that, despite the expected mediating roles of vision, purpose, and empathy, organizational resilience remains paramount for enhancing job satisfaction in a post-pandemic landscape.